Ageing, health, and productivity : the economics of increased life expectancy - Garibaldi, Pietro, 1968-; Oliveira-Martins, Joaquim; Ours, J. C. van.; Fondazione Rodolfo Debenedetti (Oxford : Oxford University Press, 2010)
Increase in life expectancy is arguably the most remarkable by-product of modern economic growth. In the last 30 years we have gained roughly 2.5 years of longevity every decade, both in Europe and the United States. This book looks closely at the challenges to the economy that this increase brings.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Longevity -- Social aspects; Labor productivity; Life span, Productive; Social medicine -- Developed countries; Medical policy -- Developed countries